Cognitive Behavioral Counseling in Minimizing Social Anxiety in High School Students - Kadek Ayu Gayatri Astha; Putu Ari Dharmayanti; Dewi Arum Widhiyanti Metra Putri (Department of Guidance and Counseling, FIP, Undiksha, 2025)
In line with its objectives, educational services in schools are expected not only to foster students’ academic development but also to ensure their social and emotional well-being as part of holistic growth. However, in practice, many students still experience high levels of social anxiety due to irrational thinking patterns and fear of negative evaluation from their social environment, which hinders learning engagement and interpersonal relationships. This study aimed to examine the effectiveness of Cognitive Behavioral Counseling using Cognitive Restructuring techniques in reducing students’ social anxiety. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The participants consisted of 14 students with high levels of social anxiety selected through purposive sampling and assigned to an experimental group and a control group, each comprising seven students. Data were collected using a social anxiety questionnaire that had met validity and reliability requirements and were supported by interviews with school counselors. Data analysis was conducted through prerequisite tests (normality and homogeneity) followed by an independent samples t-test. The results revealed a significant difference between the experimental and control groups after the intervention (p = 0.001 < 0.05), with an effect size of 3.23, indicating a very strong effect. The study concludes that Cognitive Behavioral Counseling based on cognitive restructuring is effective in reducing students’ social anxiety. These findings highlight the importance of integrating cognitive-based interventions into school counseling services as an evidence-based psychosocial support strategy.